The effect of donor and recipient race on outcomes of assisted reproduction - LIU, Yijun (Am J Obstet Gynecol, 2020)
BACKGROUND: A growing literature suggest that minority races, particularly Black women, have lower probability of live birth and higher risk of perinatal complications after autologous ART. However, questions still remain as to whether these racial disparities have arisen due to associations between race and oocyte/embryo quality, the uterine environment, or a combination of the two. Oocyte donation ART represents a unique approach to examine this question. OBJECTIVE: To evaluate the associations between the race of female oocyte donors and recipients and live birth rates following vitrified donor oocyte assisted reproductive technologies (ART). STUDY DESIGN: This was a retrospective study conducted at a single, private fertility clinic that included 327 oocyte donors and 899 recipients who underwent 1601 embryo transfer cycles (2008–2015). Self-reported race of the donor and recipient were abstracted from medical records. Live birth was defined as the delivery of at least one live born neonate. We used multivariable cluster weighted generalized estimating equations with binomial distribution and log link function to estimate the adjusted risk ratios (aRR) of live birth adjusting for donor age and BMI, recipient age and BMI, tubal and uterine factor infertility, and year of oocyte retrieval. RESULTS: The racial profile of our donors and recipients were similar: 73% White, 13% Black, 4% Hispanic, 8% Asian, and 2% Other. Women who received oocytes from Hispanic donors had a significantly higher probability of live birth (aRR 1.20, 95% CI 1.05, 1.36) compared with women who received oocytes from White donors. Among Hispanic recipients, however, there was no significant difference in probability of live birth compared with White recipients (aRR 1.07 95% CI 0.90, 1.26). Embryo transfer cycles using oocytes from Black donors (aRR 0.86, 95% CI 0.72, 1.03) and Black recipients (aRR 0.84, 95% CI 0.71, 0.99) had a lower probability of live birth compared to White donors and White recipients, respectively. There were no significant differences in the probability of live birth among Hispanic, Asian, and Other race recipients compared with White recipients. CONCLUSIONS: Black female recipients had lower probability of live birth following ART even when using vitrified oocytes from healthy donors. Female recipients who utilized vitrified oocytes from Hispanic donors had higher probability of live birth regardless of their own race.